Renaissance Papers 2021 - Pearce, Jim (Renaissance Papers., 2022)
Essays ranging from the role of early modern chess in upholding Aristotelian virtue to Sidney, Wroth, Spenser, and Shakespeare and several topics involving the New World before concluding with Holbein, Henry VIII, and Molière.